Puṭṭillu : kathā sampuṭi - Ramaṇarāvu, Ke. Vi. (Haidarābād : Viśālāndhra Pabliṣiṅg Haus, 2013)
Collection of stories on social themes.
Short stories.
"Pracuraṇa neṃ. 2350/472"--T.p. verso.
In Telugu.
Keywords: Short stories, Telugu; Short stories, Telugu